Fatal infection caused by a genetically distinct elephant endotheliotropic herpesvirus type 5 in a captive Asian elephant in Germany - Abdelgawad, Azza; Nascimento, Mariana; Prahl, Adriane; Flügger, Michael; Szentiks, Claudia A.; Holtze, Susanne; Hildebrandt, Thomas B.; Trimpert, Jakob (Virology journal, 2024)
Background Elephant endotheliotropic herpesvirus (EEHV) infection is the most common cause for lethal hemorrhagic disease in captive juvenile Asian elephants ( Elephas maximus ). Although EEHV1 is known as the most likely cause of fatal haemorrhagic disease in Asian elephants, EEHV5 was lately involved in lethal cases of haemorrhagic disease in captive elephants. Case presentation Here we report the first death of a four-year old Asian elephant diagnosed with EEHV5 in Germany. Molecular diagnosis yielded detection of EEHV5 DNA in all tested tissues. Histopathological examination revealed typical features of hemorrhagic disease in all examined organs. EEHV5 was sequenced from total DNA isolated from heart tissue by Illumina and Nanopore sequencing. Sequencing data showed 3,881 variants, distributed across the entire genome, compared to the published EEHV5 sequence. Conclusions We have detected EEHV5 in a fatal disease case of a male Asian elephant. Whole genome sequencing revealed substantial differences of our DNA isolate compared to available EEHV5 sequences. This report of fatal haemorrhagic disease associated with EEHV5 infection should raise awareness for EEHV5 as an important elephant pathogen. Genome sequencing and downstream SNPs analysis will further encourage future research to understand genetic diversity, pathogenesis and virulence of EEHVs with respect to developing new diagnostic methods, prophylactic strategies, and implementation of surveillance and control measures.